Spiritual and Moral Effect as the Result of Integration of Mathematical with Humanitarian Knowledge at Universities - Svetlana N. Dvoryatkina; Manuk A. Mkrtchyan; Svetlana A. Rozanova (National Research Mordova State University, 2018)
Introduction. The relevance of the study is determined by scientific, social and practical importance of the issues of restoring the spiritual and moral potential of young people, strengthening the civic position of our intellectual elite in the conditions of instability of socio-political, economic and socio-cultural development. It is necessary to search for innovative ways, methods and means of spiritual and moral education of modern students. The main target of the article is to develop a technology for obtaining, identifying and evaluating the synergistic spiritual and moral effect when the mathematical departments introduce the elements of the spiritual and moral education of students to the higher school educational process through the integration of mathematical and humanitarian knowledge. Materials and Methods. The methodological foundations of the study are the ideas and the principles of synergetic approach and integrative education. The important part is assigned also to methods of the system analysis, comparison, experimental and statistical methods. Results. The complex technology of teaching mathematics with synergetic spiritual and moral effect understood as the pedagogical mechanism of integration of knowledge and diagnostic tools of identification and assessment of this type of effect is developed and introduced. Modernisation of the syllabus of integrative course for students linguists with elaboration of some modules by inclusion of questions of spiritual and moral subject is carried out. Criteria of manifestation of spiritual and moral effect are marked out and psychodiagnostic tools of the analysis and assessment of this phenomenon and its structural components are offered. The prospects of use of the developed technology for the technical directions of preparation and other scientific and pedagogical purposes are defined. Discussion and Conclusions. Introduction of the developed technology allowed to reveal a potential for realisation of spiritual and moral education of students at mathematical departments. Owing to its universality the technology can be used during the organisation of educational processes for a wide range of specialties, courses and academic programmes. Results of current research have novelty equipping the higher school with author's technology and techniques; they give the opportunity to bring the education of a person to a further level.